2016
DOI: 10.1371/journal.pone.0155479
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Resistance Patterns of Bacterial and Fungal Colonization of Biliary Plastic Stents: A Prospective Cohort Study

Abstract: BackgroundPlastic stents used for the treatment of biliary obstruction will become occluded over time due to microbial colonization and formation of biofilms. Treatment of stent-associated cholangitis is often not effective because of inappropriate use of antimicrobial agents or antimicrobial resistance. We aimed to assess the current bacterial and fungal etiology of stent-associated biofilms, with particular emphasis on antimicrobial resistance.MethodsPatients with biliary strictures requiring endoscopic sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Reflecting their differing virulence, and in agreement with a recent large multicenter trial on biliary infections, enterobacterales comprised almost 60% and enterococci only 20% of blood culture isolates [2]. In line with previous studies, our multivariate analysis found the presence of a biliary prosthesis an independent predictor for enterococcal isolation from bile [3,9,12,13]. The Tokyo guideline recommends empirical treatment covering enterococci in severe community-acquired cholangitisand in health-care associated infections if patients are colonized or enterococci are otherwise of concern.…”
Section: Discussionsupporting
confidence: 88%
“…Reflecting their differing virulence, and in agreement with a recent large multicenter trial on biliary infections, enterobacterales comprised almost 60% and enterococci only 20% of blood culture isolates [2]. In line with previous studies, our multivariate analysis found the presence of a biliary prosthesis an independent predictor for enterococcal isolation from bile [3,9,12,13]. The Tokyo guideline recommends empirical treatment covering enterococci in severe community-acquired cholangitisand in health-care associated infections if patients are colonized or enterococci are otherwise of concern.…”
Section: Discussionsupporting
confidence: 88%
“…were isolated from 55.9% of the patients [13]. Due to these high rates of bacterial colonization, the authors suggested microbiological testing of explanted biliary stents as a helpful diagnostic procedure to identify the causative pathogens of AC [13]. Schneider et al .…”
Section: Discussionmentioning
confidence: 99%
“…found in patients who had undergone BD stenting [10]. Bile from healthy individuals is sterile; however, in patients with BD pathologies, bacterial or fungal colonization of the bile without clinical signs of infection may occur [11,12] in up to 100% of patients with biliary stents [13], which can be difficult to discriminate from AC [14]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to Gram staining or immunohistochemical methods, FISH combines molecular detection of microorganisms with fluorescence microscopy and has been increasingly used for analysis of biofilm‐associated infections . FISH can be applied to in vitro samples as well as to ex vivo samples from animal models or patients . Since FISH‐probes hybridize ribosomal RNA, the signal intensity correlates to the ribosome content and consequently activity of the cells.…”
Section: Bacteriological Aspects Of Odri Studiesmentioning
confidence: 99%